Quantitative biomechanical analysis of fracture patterns in ipsilateral femoral neck and shaft fractures: an in-silico study - Xiong, Zhongwei; Liu, Zihao; Zhou, Houquan; Zhang, Xiang; Chen, Jialei (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionIpsilateral femoral neck and shaft fractures (IFN-SFs) caused by high-energy trauma pose a significant risk of complications related to bone healing. Prompt identification of fracture types and maintenance of fracture fixation stability can mitigate this risk. This study employed finite element analysis to evaluate biomechanical parameters for the stability of fixation in IFN-SFs and quantify differences in biomechanical stability among various fracture types.MethodsPatient-specific femur models were constructed from computed tomography data of 10 individuals. Simulating combinations of three Pauwels classifications (I-III) of femoral neck fractures (FNFs) and three femoral shaft fracture (FSF) types (transverse, wedge-shaped, comminuted), a total of 90 FNF-FSF models were generated. Reconstruction nails with cannulated screws were used to fix the fracture models, and postoperative single-leg standing loads were simulated. The entropy method comprehensively evaluated biomechanical parameters to assess the fixation stability for different fracture types.ResultsAmong fracture types, Pauwels Type III FNF combined with comminuted FSF showed the lowest stability (composite score = 0.22), while Pauwels Type I FNF with transverse FSF was the most stable (composite score = 0.79). Maximum implant stress (weight = 24.5%) and maximum proximal-distal femur interfragmentary motion (weight = 17.1%) were the most influential biomechanical parameters for assessing IFN-SF stability.ConclusionFor IFN-SFs, the FNF type primarily dictates fixation stability, with the FSF contributing synergistically. Maximum implant stress and proximal-distal femur interfragmentary motion are key biomechanical indicators for assessing IFN-SFs. Personalized enhanced fixation strategies are essential for ipsilateral Pauwels Type III FNF and comminuted FSF.